Extensive temporomandibular joint ankylosis involving medial pterygoid plates and the maxillary tuberosity- a case report - Sujay M. Bhave; Divya Mehrotra; Praveen Singh; Anand Shukla (Elsevier, 2019)
Background: Temporomandibular joint ankylosis is a distressing condition which leads to significant functional debility and facial blemish. It can be surgically managed with gap or interposition arthroplasty, with an objective to restore joint function and prevent re-ankylosis. Sometimes TMJ ankylosis can present with atypical presentations like skull base ankylosis. The main aim of this surgery is to successfully treat such conditions efficiently without any possible complications. However, surgical procedures for such atypical presentations in this disease are rarely reported. Case summary: Here we report a 27 year old male with Left TMJ ankylosis involving the skull base. The patient presented with reduced mouth opening with a previous history of trauma. For treatment we performed a surgery by doing osteoarthrectomy with interpositional arthroplasty of left TMJ using piezosurgery. To our knowledge this is the only TMJ ankylosis case with involvement of bones of the skull base treated with piezosurgery. Intraoperatively we achieved a mouth opening of 30 mm, and postoperatively after 15 days mouth opening up to 30 mm was achived with physiotherapy. Conclusion: Some times TMJ ankylosis can present with atypical presentations in which bones of the skull base are involved. These are very rare and could be termed as 'skull base ankylosis'. Such cases can be surgically challenging and some surgical treatment modalities like Computer Assisted Surgery (CAS), 3D Navigation and Piezo-electric surgery could be beneficial in avoiding complications and facilitating efficient treatment.